Redistribution of elements between wastes and organic-bearing material in the dispersion train of gold-bearing sulfide tailings: Part I. Geochemistry and mineralogy; Science of The Total Environment; Vol. 581-582 - Saryg-ool B. Yu. Bagai-ool; Myagkaya I. N. Irina Nikolaevna; Kirichenko I. S.; Gustaitis M. A. Mariya Alekseevna; Shuvaeva O. V. Olga; Zhmodik S. M. Sergey Mikhaylovich; Lazareva E. V. Elena Vladimirovna (2017, 2017)
Title screen